Hubungan Antara Kelincahan Dengan Kemampuan Dribbling Dalam Permainan Sepak Bola Pada Mahasiswa Jurusan POR FIKKM UNIMA - Jodi Dadamuda (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
This study aims to determine the correlation between agility and dribbling ability in football among students of the Department of Physical Education at FIKKM UNIMA. The research applied a descriptive method with a correlational approach. A total of 20 male students were randomly selected. Data collection instruments included an agility test (4×10 meter shuttle run) and a zig-zag dribbling test using a stopwatch. The analysis revealed a correlation coefficient (r) of 0.91, indicating a very strong relationship, with a contribution of 82.81%. The significance test showed tcount = 9.312 > ttable = 2.101 (p < 0.05), confirming a significant relationship between agility and dribbling ability.